Kick impact characteristics for different rugby league kicks - Ball, K. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Kicking is becoming increasingly important in rugby league and one of the most important aspects of kicking is the nature of impact. This study examined impact characteristics for five rugby league kicks - the goalshot, the punt kick, the dropkick, the grubber and the 'bomb'. Seven elite players performed these kicks while being videoed (6000Hz). Digitised data of nine points (five on the kick leg, four on the ball) were used to quantify parameters near and during impact. Rugby league kicks produced a smaller time in contact and a larger amount of work compared to kicks in other sports. Differences also existed between the five types of rugby league kick tested in terms of ball to foot ratio and foot and ball positioning at impact. These differences between kicks within the same sport highlight the need to evaluate different kick types separately within a sport.